MANAJEMEN KOMUNIKASI KOMUNITAS SATOE ATAP DALAM GERAKAN SOSIAL PENDIDIKAN ANAK KELUARGA PRA SEJAHTERA - Faradila, Sabna; Luqman, Yanuar; Suryanto Gono, Joyo Nur (Interaksi Online, 2024)
Numerous social education communities have emerged to support the education of children by providing free learning facilities, relying on support from external parties for the implementation of their activities. However, this support is voluntary, making it irregular and uncertain, posing challenges and obstacles for the community in carrying out its initiatives. This research aims to investigate how the Satoe Atap community manages to secure support to aid the education of underprivileged families' children. It employs a qualitative research approach using a case study method within the post-positivism paradigm. Data collection techniques involve in-depth interviews with pattern-matching analysis. The research incorporates Anthony Giddens' Structuration Theory and John A. Ledingham's Relationship Management Theory. The findings indicate that Satoe Atap's communication management to obtain support is achieved through several methods. The planning process is documented through regular meeting activities. The execution process is evident in every activity conducted by Satoe Atap, such as managing social media, organizing events, and maintaining relationships with those who have previously assisted them. As a form of evaluation, Satoe Atap consistently assesses its activities to implement improvements for future events. However, the research results reveal that Satoe Atap has not fully implemented two-way relationship maintenance with all parties, and the community lacks specialized training for its internal management team.